Bridging the gap: Needs assessment of science teacher in-service education in Turkey and the effects of teacher and school demographics - BEKİROĞLU, FERAL (My University, 2007)
Turkish science teachers' in-service needs and the effects of teacher and school demographic variables on these needs are examined in this study. In addition, major barriers that prevented science teachers from attending in-service programmes are investigated. The data for the research were gathered through a survey. This study shows that Turkish science teachers require more instructional materials, laboratory equipment, computers, and software and need in-service education to integrate these instructional facilities into their lessons. This study also indicates that teacher and school demographic variables have little significance in predicting science teachers' needs.